An Automated Optical Strain Measurement System for Estimating Polymer Degradation under Fatigue Testing; Sensors; Vol. 22, iss. 16 - Bogdanov A. A. Aleksey Alekseevich; Panin A. V. Alexey Viktorovich; Lyubutin P. S. Pavel Stepanovich; Eremin A. V. Alexandr Vyacheslavovich; Buslovich D. G. Dmitry Gennadjevich; Byakov A. V. Anton Viktorovich (2022, 2022)
Title screen